Innovative Work Performance as Mediation Organizational Culture On Employee Performance - I Wayan Gde Sarmawa; Ida Ayu Oka Martini; Ida Ayu Putu Widani Sugianingrat; Anak Agung Dwi Widyani; Ni Ketut Karwini (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThe purpose of this study was to analyze (1) the influence of organizational culture on positive work behavior; (2) the influence of organizational culture and innovative work behavior on employee performance; and (3) the role of innovative work behavior in mediates the relationship of organizational culture with employee performance. The study was conducted at the Rural Credit Bank (RCB) in Badung Regency, Bali Province. The number of research samples is 52 RCB. The respondents in this study are 156 employees. The data is analyzed using SmartPLS 3.2.8 program. The result shows that organizational culture shows a significant positive effect on innovative work behavior. Work culture and innovative work behavior also have a significant positive effect on employee performance at RCB. It is concluded that innovative work behavior acts as a mediator in the relationship between organizational culture and the performance of RCB employees. Keywords: organizational culture, innovative work behavior, employee performance Prestasi Kerja Inovatif Sebagai Mediasi Budaya Organisasi Terhadap Kinerja Karyawan AbstrakTujuan penelitian ini adalah untuk menganalisis (1) pengaruh budaya organisasi terhadap perilaku kerja positif; (2) pengaruh budaya organisasi dan perilaku kerja inovatif terhadap kinerja pegawai; dan (3) peran perilaku kerja inovatif dalam memediasi hubungan budaya organisasi dengan kinerja pegawai. Penelitian dilakukan di Bank Perkreditan Rakyat (BPR) di Kabupaten Badung, Provinsi Bali. Jumlah sampel penelitian adalah 52 RCB. Responden dalam penelitian ini adalah 156 karyawan. Data dianalisis menggunakan program SmartPLS 3.2.8. Hasil penelitian menunjukkan bahwa budaya organisasi berpengaruh positif signifikan terhadap perilaku kerja inovatif. Budaya kerja dan perilaku kerja inovatif juga berpengaruh positif signifikan terhadap kinerja karyawan di RCB. Disimpulkan bahwa perilaku kerja inovatif berperan sebagai mediator dalam hubungan antara budaya organisasi dengan kinerja pegawai RCB. Kata kunci: budaya organisasi, perilaku kerja yang inovatif, kinerja karyawan